PEG-PLGA nano drug-loaded particle for enhancing oral absorption of trimethoprim and preparation method of PEG-PLGA nano drug-loaded particle
Through the preparation method of PEG-PLGA nano-drug-carrying particles, the problems of low solubility and bioavailability of trimethoprim were solved, high drug loading and stability were achieved, and its oral bioavailability and therapeutic effect were significantly improved.
Patent Information
- Application Number
- CN202510728475.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-03
- Publication Date
- 2025-08-29
AI Technical Summary
The poor water solubility of trimethoprim, short half-life of elimination and low oral bioavailability, limits its effectiveness in clinical applications.
The emulsion solvent evaporation method of PEG-PLGA nanomedicine-loading particles was prepared by mixing trimethoprim, polyethylene glycol and polylactic acid-glycolic acid copolymers under specific ratios and conditions to form an organic phase and aqueous phase. Nanoparticles with high drug loading and encapsulation rate were prepared by ultrasonic, evaporation, centrifugation and lyophilization treatment.
It improves the solubility and bioavailability of trimethoprim, extends the elimination half-life, enhances the oral absorption effect, shows excellent stability and sustained release characteristics, and significantly improves bioavailability.
Smart Images

Figure CN120549893A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of nano drug-loaded particles, and in particular to PEG-PLGA nano drug-loaded particles for enhancing oral absorption of trimethoprim and a preparation method thereof. Background Art
[0002] Trimethoprim (TMP), a sulfonamide antimicrobial synergist, holds a crucial position in antimicrobial therapy due to its broad-spectrum antimicrobial activity, low side effects, and significant post-antibiotic effects. Its mechanism of action is the specific inhibition of dihydrofolate reductase, blocking the conversion of dihydrofolate to tetrahydrofolate, thereby interfering with folate metabolism and enhancing the activity of sulfonamides. This mechanism underpins its clinical application, particularly in combination with sulfamethoxazole (co-trimoxazole), which exhibits significant efficacy against respiratory tract infections caused by Streptococcus pneumoniae and Haemophilus influenzae. Furthermore, TMP is also effective in treating urinary tract infections, typhoid fever, and gastrointestinal infections caused by Escherichia coli. TMP-sulfonamide combinations are also widely used in veterinary medicine to prevent and treat Escherichia coli infections in pigs and coccidiosis in birds. However, TMP's poor water solubility, short elimination half-life (t½), and low oral bioavailability severely limit its clinical application. It is worth noting that TMP has a very high solubility (>1000 mg / mL) in a low pH environment (pH < 2), and its oral bioavailability may be improved by reducing gastric release. Therefore, it is crucial to develop new formulations of trimethoprim with sustained-release properties.
[0003] To improve the solubility of TMP, researchers have attempted inclusion technology with β-cyclodextrin and its derivatives. While this significantly improved aqueous solubility, in vivo studies have been lacking to validate its bioavailability enhancement. Nanodelivery technology, with its advantages of small particle size, high bactericidal efficiency, and reduced resistance induction, offers new avenues for optimizing antibacterial therapy. While PLGA-loaded TMP has demonstrated excellent performance in the topical treatment of urinary tract infections, its oral potential remains underexplored. Although PEGylated nanostructured lipid carriers have improved oral delivery of the TMP / sulfamethoxazole combination, the low drug loading of 9.8% limits its application. Studies have demonstrated that insufficient drug loading impairs nanoparticle adsorption and transmembrane penetration, resulting in intracellular drug concentrations below the minimum inhibitory concentration (MIC), reducing antibacterial efficacy. Therefore, the development of new TMP formulations with high drug loading, enhanced stability, and improved oral bioavailability is urgently needed.
[0004] Biodegradable polymer nanoparticles are important carriers for improving drug efficacy. For example, PLGA decomposes into carbon dioxide and water in the body and is excreted through metabolism. However, its hydrophobic surface is easily recognized by plasma opsonins, mediating rapid clearance by the mononuclear phagocytic system (MPS), significantly shortening circulation time. Hydrophilic PEG modification can inhibit opsonin adsorption through steric hindrance and form a dense hydration layer on the particle surface, imparting "stealth" properties to the nanoparticles and extending circulation time. As the preferred modifier for PLGA-based long-circulating particles, PEG can adjust the zeta potential to near neutrality, enhance steric stability in biological media, and improve the encapsulation efficiency of poorly soluble drugs. For example, PLGA-PEG nanoparticles can achieve a drug loading of over 32% for the poorly soluble antifibrotic drug pirfenidone, significantly improving drug stability and sustained-release properties. Studies have shown that PEG-PLGA can enhance the solubility and cellular uptake of isoliensinine and promote its distribution to key tissues such as the heart, liver, lungs, and kidneys, ultimately improving bioavailability. Based on this, the use of PEG-PLGA to modify TMP nanoparticles has become an innovative strategy to overcome its poor solubility, low drug loading and insufficient bioavailability. Summary of the Invention
[0005] The present invention aims to provide a PEG-PLGA nanoparticle for enhancing the oral absorption of trimethoprim and a preparation method thereof, so as to solve the technical problems of poor water solubility, short elimination half-life and low oral bioavailability of trimethoprim.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing PEG-PLGA nanoparticles for enhancing oral absorption of trimethoprim, comprising the following steps:
[0008] 1) dissolving trimethoprim, polyethylene glycol, and poly(lactic acid-co-glycolic acid) in organic solvents to obtain a trimethoprim solution, a polyethylene glycol solution, and a poly(lactic acid-co-glycolic acid) solution, respectively;
[0009] 2) adding the trimethoprim solution dropwise to the polyethylene glycol solution, and performing ultrasonic treatment to obtain a mixture solution;
[0010] 3) adding the mixture solution to the poly(lactic acid-co-glycolic acid) solution to form an organic phase;
[0011] 4) using polyvinyl alcohol solution as the aqueous phase, mixing the organic phase and the aqueous phase, and then performing ultrasonic treatment, evaporation, washing, and centrifugation in sequence to collect the precipitate;
[0012] 5) Ultrasonic dispersion of the precipitate in water, followed by freeze-drying to obtain drug-loaded nanoparticles.
[0013] Furthermore, in the step 1), the organic solvent comprises dichloromethane, and the mass ratio of the trimethoprim, polyethylene glycol and polylactic acid-glycolic acid copolymer is 30-45:80-110:350-450.
[0014] Furthermore, the mass concentration of the trimethoprim solution is 1.5-4 mg / mL, the mass concentration of the polyethylene glycol solution is 6-7 mg / mL, and the mass concentration of the polylactic acid-glycolic acid copolymer solution is 22-30 mg / mL.
[0015] Furthermore, the mass concentration of the polyvinyl alcohol solution is 0.5-2%, and the volume ratio of the water phase to the oil phase is 2-5:1.
[0016] Furthermore, in step 2) and step 4), the ultrasonic treatment is intermittent ultrasonic treatment, with a pulse cycle of: ultrasonic 4 seconds / pause 2 seconds; the ultrasonic treatment power is 200-300W, and the ultrasonic treatment time is independently 1-10 minutes.
[0017] Furthermore, the evaporation temperature is 30-40° C., and the evaporation time is 5-20 minutes.
[0018] Furthermore, the centrifugal speed is 14000-25000 rcf, the centrifugal time is 20-40 min, and the centrifugation is performed at 0-10°C.
[0019] Furthermore, the freeze-drying treatment temperature is -90 to -70°C, and the freeze-drying treatment time is 20 to 30 hours.
[0020] The present invention also provides a PEG-PLGA nano drug-loaded particle for enhancing the oral absorption of trimethoprim.
[0021] Beneficial effects of the present invention:
[0022] The present invention successfully prepared PEG-PLGA nanoparticles using an emulsion solvent evaporation method as an effective oral delivery system for TMP to improve its solubility and bioavailability. The nanoparticles obtained by this method have a high drug loading (LC) of 34.0±1.6% and an encapsulation efficiency (EE) of 88.2±4.3%, a uniform particle size (245±40 nm), and a low PDI of 0.103±0.019. These nanoparticles exhibit excellent stability: they maintain stable physicochemical properties after storage at 4°C for 30 days, and the encapsulation efficiency does not change significantly in acidic media, indicating that they can maintain structural integrity in the gastric fluid environment. In vitro release studies show that the PEG-PLGA / TMP nanoparticles have sustained release characteristics, exhibiting a biphasic release pattern in a pH 1.2 medium and accelerated release in a pH 6.8 medium. The release behavior conforms to the first-order kinetic model, with Fickian diffusion as the dominant factor. PXRD analysis confirmed that TMP existed in an amorphous state, resulting in a cumulative release rate of 86% over 48 hours at pH 6.8. In vivo pharmacokinetic studies showed that compared with free TMP, PEG-PLGA / TMP nanoparticles significantly prolonged the elimination half-life (t1 / 2) of TMP to 2.47±0.19 hours (0.72±0.08 hours for free TMP), and increased oral bioavailability by 2.82 times due to prolonged circulation time in the body and reduced degradation in the gastric environment. In vitro-in vivo correlation analysis showed that the coefficient of determination (R 2 ) was 0.9623, further verifying the reliability of the PEG-PLGA / TMP nanoparticle design, and its in vitro release curve can effectively predict the in vivo absorption kinetics. These results show that the PEG-PLGA / TMP nanoparticles not only address the inherent defects of TMP (such as low solubility and rapid clearance), but also significantly improve its oral bioavailability. The PEG-PLGA / TMP nanoparticles of the present invention have the potential to replace traditional formulations, and are expected to reduce the frequency of administration and improve the treatment effect of bacterial infections. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The scanning electron microscope image, PDI distribution diagram and Zeta potential diagram of the PEG-PLGA / TMP drug-loaded nanoparticles of Example 1 of the present invention are shown;
[0024] Figure 2 The X-ray diffraction pattern and Fourier transform infrared spectrum of the PEG-PLGA / TMP drug-loaded nanoparticle freeze-dried powder prepared in Example 1 of the present invention;
[0025] Figure 3 The graph shows the particle size, polydispersity index (PDI), zeta potential change, and encapsulation efficiency change of the PEG-PLGA / TMP drug-loaded nanoparticles prepared in Example 1 of the present invention;
[0026] Figure 4 This is a cumulative release curve of the PEG-PLGA / TMP drug-loaded nanoparticles prepared in Example 1 of the present invention under acidic conditions;
[0027] Figure 5 This is the plasma drug concentration curve of rats after oral administration of TMP and PEG-PLGA / TMP nanoparticles;
[0028] Figure 6 This is a correlation curve between the in vitro cumulative release rate and the in vivo absorption rate of PEG-PLGA / TMP nanoparticles. DETAILED DESCRIPTION
[0029] The present invention provides a method for preparing PEG-PLGA nanoparticles for enhancing oral absorption of trimethoprim, comprising the following steps:
[0030] 1) dissolving trimethoprim, polyethylene glycol, and poly(lactic acid-co-glycolic acid) in organic solvents to obtain a trimethoprim solution, a polyethylene glycol solution, and a poly(lactic acid-co-glycolic acid) solution, respectively;
[0031] 2) adding the trimethoprim solution dropwise to the polyethylene glycol solution, and performing ultrasonic treatment to obtain a mixture solution;
[0032] 3) adding the mixture solution to the poly(lactic acid-co-glycolic acid) solution to form an organic phase;
[0033] 4) using polyvinyl alcohol solution as the aqueous phase, mixing the organic phase and the aqueous phase, and then performing ultrasonic treatment, evaporation, washing, and centrifugation in sequence to collect the precipitate;
[0034] 5) Ultrasonic dispersion of the precipitate in water, followed by freeze-drying to obtain drug-loaded nanoparticles.
[0035] In the present invention, in step 1), the organic solvent is preferably dichloromethane, and the mass ratio of trimethoprim, polyethylene glycol and polylactic acid-co-glycolic acid is 30-45:80-110:350-450, preferably 32-40:90-100:380-420, and more preferably 39:97.5:390.
[0036] In the present invention, the mass concentration of the trimethoprim solution is 1.5-4 mg / mL, preferably 2-3 mg / mL; the mass concentration of the polyethylene glycol solution is 6-7 mg / mL, preferably 6.5 mg / mL; the mass concentration of the polylactic acid-co-glycolic acid solution is 22-30 mg / mL, preferably 26 mg / mL.
[0037] In the present invention, the mass concentration of the polyvinyl alcohol solution is 0.5-2%, preferably 0.5-1%, and more preferably 0.5%; the volume ratio of the water phase to the oil phase is 2-5:1, preferably 2:1.
[0038] In the present invention, in step 2) and step 4), the ultrasonic treatment adopts intermittent ultrasonic treatment, and the pulse cycle is: ultrasonic 4 seconds / pause 2 seconds; the power of ultrasonic treatment is 200-300W, preferably 300W; the time of ultrasonic treatment is independently 1-10 minutes, preferably 1-5 minutes.
[0039] In the present invention, the evaporation temperature is 30-40° C., preferably 35-37° C.; the evaporation time is 5-20 min, preferably 10 min. The purpose of evaporation is to quickly remove the organic solvent, and the purpose of washing is to remove unencapsulated drugs.
[0040] In the present invention, the centrifugal speed is 14000-25000 rcf, preferably 20000 rcf; the centrifugal time is 20-40 min, preferably 30 min; and the centrifugation is carried out at 0-10°C, preferably 4-8°C.
[0041] In the present invention, the freeze-drying treatment temperature is -90 to -70°C, preferably -80°C; the freeze-drying treatment time is 20 to 30 hours, preferably 24 hours.
[0042] The present invention also provides a PEG-PLGA nano drug-loaded particle for enhancing the oral absorption of trimethoprim.
[0043] The raw materials used in the present invention are:
[0044] Trimethoprim (purity > 98.0%) was purchased from Tokyo Chemical Industry Co., Ltd. (TCI, Japan). Poly (D, L-lactide-glycolide) (PLGA; 504H (lactide:glycolide ratio of 50:50, carboxyl end groups, molecular weight 38,000–54,000), polyethylene glycol (PEG; molecular weight 5,500–7,500), polyvinyl alcohol (PVA; molecular weight 13,000–23,000), and hydrochloric acid (HCl) were purchased from Sigma-Aldrich (MA, USA). Dichloromethane (DCM) was provided by Tianjin Xinbote Chemical Co., Ltd. (Tianjin, China). Reagent-grade solvents such as methanol (MeOH) and formic acid used for ultra-performance liquid chromatography (UPLC) and ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS / MS) analyses were purchased from Fisher Chemical Company (New Hampshire, USA). Phosphate-buffered saline (PBS) was purchased from Biosun Biotechnology Co., Ltd. (Beijing, China). Dialysis membrane (molecular weight cutoff 8,000–14,000 Da) was provided by Solebro Life Sciences Co., Ltd. (Beijing, China). All experiments were performed using ultrapure water prepared by a Milli-Q system from Millipore.
[0045] The technical solutions provided by the present invention are described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0046] Example 1
[0047] TMP (39 mg), PEG (97.5 mg), and PLGA (390 mg) were dissolved in dichloromethane (DCM) to yield a 3 mg / mL TMP solution, a 6.5 mg / mL PEG solution, and a 26 mg / mL PLGA solution, respectively. The TMP solution was added dropwise to the PEG solution under continuous stirring, followed by sonication at 300 W for 1 minute (pulse cycle: 4 seconds sonication / 2 seconds pause). This mixture was slowly added to the PLGA solution in an ice-water bath with magnetic stirring to form an organic phase. The aqueous phase consisted of a 10 mL volume of 0.5% (w / v) polyvinyl alcohol (PVA) solution. 5 mL of the organic and aqueous phases were mixed in an ice-water bath and emulsified by intermittent sonication at 300 W for 5 minutes (pulse cycle: 4 seconds sonication / 2 seconds pause). The organic solvent was then rapidly removed by vacuum evaporation at 37°C for 10 minutes. Finally, the suspension was washed three times to remove unencapsulated drug, and the precipitate was collected by centrifugation at 20,000 rcf for 30 min at 4°C. The collected precipitate was redispersed in distilled water and sonicated for 10 min to prepare nanoparticles with good fluidity. The particles were then frozen and lyophilized at -80°C for 24 h to obtain PEG-PLGA / TMP nanoparticles.
[0048] Example 2
[0049] Same as Example 1, except that the concentration of the TMP solution is 1.5 mg / mL.
[0050] Example 3
[0051] Same as Example 1, except that the concentration of the TMP solution is 4 mg / mL.
[0052] Example 4
[0053] Same as Example 1, except that the concentration of the polyvinyl alcohol solution is 1%.
[0054] Example 5
[0055] Same as Example 1, except that the concentration of the polyvinyl alcohol solution is 2%.
[0056] Example 6
[0057] Same as Example 1, except that the ultrasonic frequency in the preparation step is replaced with 200W.
[0058] Example 7
[0059] Same as Example 1, except that the ultrasonic frequency in the preparation step is replaced with 250W.
[0060] The PEG-PLGA / TMP drug-loaded nanoparticles obtained in Example 1 were subjected to the following experimental tests:
[0061] Experimental Example 1: Nanoparticle Characterization
[0062] 1. Particle size, polydispersity index (PDI), zeta potential and scanning electron microscopy (SEM) analysis
[0063] The particle size, polymer dispersion index (PDI) and Zeta potential of PEG-PLGA / TMP nanoparticles were measured three times using a dynamic light scattering instrument (ZetasizerNano S90, Malvern Instruments, UK). The samples were diluted with ultrapure water and analyzed at 25°C and a detection angle of 90°. For morphological characterization, the freeze-dried nanoparticles were placed on an aluminum sample stage and gold-plated. A Gemini 360 field emission scanning electron microscope (Zeiss, Germany) was used for observation at an accelerating voltage of 5-15 kV. The results are shown in Figure 2. Figure 1 shown.
[0064] 2. Fourier transform infrared spectroscopy (FTIR) analysis
[0065] FTIR analysis was performed using an IRTracer-100 spectrometer (Shimadzu Corporation, Japan). Samples were prepared by mixing 2 mg of TMP, PEG, PLGA, or PEG-PLGA / TMP drug-loaded nanoparticles with 200 mg of potassium bromide (KBr) using a standard tableting method.-1 Spectra are collected within the wavenumber range with a resolution of 4 cm -1 (32 scans per sample).
[0066] 3. Powder X-ray diffraction (PXRD) analysis
[0067] The XRD patterns of freeze-dried PEG-PLGA / TMP nanopowders, pure TMP, PLGA, PEG, and their physical mixtures were characterized using an X-ray powder diffractometer (Bruker D8 Advance, Germany) equipped with a CuKα radiation source. Diffraction data were collected at room temperature over a 2θ angle range of 5–80° at a scan rate of 5° / min.
[0068] Experimental Example 2: Determination of drug loading and encapsulation efficiency
[0069] Ultra-performance liquid chromatography (UPLC) was used to determine the free TMP content, and the drug loading (LC) and encapsulation efficiency (EE) were calculated. The drug loading (LC) and encapsulation efficiency (EE) of the PEG-PLGA / TMP drug-loaded nanoparticles were determined by UPLC. Analyses were performed on an Agilent 1290 UPLC system (Agilent Technologies, USA) equipped with a diode array detector (DAD) using an Agilent ZORBAX Eclipse Plus-C18 column (4.6 × 250 mm, 5 μm). The mobile phase consisted of 0.1% formic acid in water (A) and 0.1% formic acid in methanol (B). The gradient elution program is detailed in Table 1. Chromatographic conditions included a flow rate of 1 ml / min, an injection volume of 5 μl, a detection wavelength of 280 nm, and a column temperature maintained at 30°C. All solutions were filtered through a nylon 66 filter (pore size 0.45 μm, Millipore) before injection.
[0070] Table 1 Ultra-performance liquid chromatography (UPLC) gradient elution method for determining drug loading (LC) and encapsulation efficiency (EE) of PEG-PLGA / TMP nanoparticles
[0071] Time (min) Mobile phase A Mobile phase B 0 80 20 1 80 20 7 20 80 8 20 80 9 80 20 13 80 20
[0072] Collect the supernatant of the nanosuspension after centrifugation and washing. The above-mentioned UPLC method is used to determine the content of free trimethoprim (TMP) in the supernatant, and then calculate the encapsulation efficiency (EE). Accurately weigh the lyophilized powder of PEG-PLGA / TMP nanoparticles prepared in Example 1 and calculate the drug loading (LC). The calculation formulas of EE and LC are as follows (1)(2):
[0073]
[0074] Among them, W total 、W free and Wdried represent the total mass of trimethoprim (TMP), the mass of free TMP in the supernatant, and the mass of freeze-dried PEG-PLGA / TMP drug-loaded nanoparticle powder, respectively.
[0075] Figure 1 The scanning electron microscope image, PDI distribution diagram and Zeta potential diagram of the PEG-PLGA / TMP drug-loaded nanoparticles prepared in Example 1 are shown. The surface morphology of the obtained samples was studied by scanning electron microscopy (SEM). Figure 1 As shown in Figures AB, the PEG-PLGA / TMP nanoparticles are spherical with a concentrated particle size distribution in the range of 200-300 nm. Dynamic light scattering measurements of the optimized formulation showed an average particle size of 245 ± 40 nm ( Figure 1 C), which is consistent with the SEM results. The low polydispersity index (PDI) of about 0.1 indicates that the PEG-PLGA / TMP nanoparticles are monodisperse and show almost no particle aggregation. In addition, the average Zeta potential, encapsulation efficiency (EE), and drug loading (LC) of the PEG-PLGA / TMP nanoparticles were measured to be -23.8±1.2 mV ( Figure 1 D), 88.2±4.3% and 34.0±1.6%, and the results are shown in Table 2. It is worth mentioning that PEG-PLGA exhibits a higher drug encapsulation efficiency when encapsulating low water-soluble drugs due to its characteristics suitable for freeze-drying.
[0076] Table 2 Physicochemical properties of PEG-PLGA / TMP drug-loaded nanoparticles of Example 1
[0077] Particle size (nm) PDI Zeta potential (mV) LC (%) EE (%) 245±40 0.103±0.019 -23.8±1.2 34.0±1.6 88.2±4.3
[0078] Figure 2 The X-ray diffraction pattern and Fourier transform infrared spectrum of the freeze-dried powder of PEG-PLGA / TMP nanoparticles prepared in Example 1. The crystallinity and physical state of the PEG-PLGA / TMP nanoparticles and their components were analyzed by powder X-ray diffraction (PXRD). Figure 2A). The PXRD pattern provides strong evidence for the successful preparation of PEG-PLGA / TMP drug-delivered nanoparticles. TMP exhibits sharp and intense peaks at diffraction angles of 11.8°, 15.1°, 17.5°, 22.2°, 25.9°, 30.7°, and 33.4°, indicating the drug's crystalline state. Due to its amorphous state, PLGA exhibits a dome-shaped diffuse scattering peak within the 2θ range of 15°-25°. The diffraction pattern of PEG exhibits two peaks at 19.2° and 23.4°, indicating its crystallinity. Notably, the PXRD pattern of the PEG-PLGA / TMP drug-delivered nanoparticles lacks any diffraction peaks associated with TMP, indicating that TMP exists in an amorphous state within the nanoparticles due to the strong interaction between the drug and the polymer matrix.
[0079] Fourier transform infrared spectroscopy (FTIR) of PEG-PLGA / TMP nanoparticles and their components is shown in Figure 2. Figure 2 B. TMP at 3471cm -1 and 3318cm -1 The characteristic peak corresponding to -NH2 stretching vibration is 1130cm -1 The peak at 2957 cm-1, which belongs to the CO stretching vibration, disappeared in the nanoparticles, indicating that the intermolecular hydrogen bonds of the TMP drug were destroyed. In addition, several new peaks were detected in the PEG-PLGA / TMP nanoparticles, including the CH stretching vibration peak of PEG-PLGA (2957 cm-1). -1 ), the shifted C=O stretching vibration band (1760cm -1 , compared with 1750cm of PLGA -1 ) and COC vibration peak (1172cm -1 and 1093cm -1 ), which together indicate that hydrogen bonds were formed between TMP and the ester carbonyl groups of PLGA. These results demonstrate that TMP was successfully encapsulated in an amorphous form within PEG-PLGA nanoparticles through intermolecular interactions.
[0080] Experimental Example 3: Stability Test of Nanoparticles
[0081] like Figure 3 As shown in FIG, the changes in particle size, polydispersity index (PDI) and zeta potential of the drug-loaded nanoparticles of Example 1 stored at different temperatures (4°C and 25°C) for 30 days were tested ( Figure 3A, B, C). At 4°C, the PEG-PLGA / TMP drug-loaded nanoparticles maintained stable physicochemical properties, with a particle size range of 240-300 nm, a PDI always below 0.16, and an absolute value of the Zeta potential below 20 mV. In contrast, the fluctuations of the three parameters increased significantly when stored at 25°C, indicating a decrease in stability under room temperature conditions. These results strongly suggest that freeze-dried PEG-PLGA / TMP drug-loaded nanoparticles should be refrigerated. In addition, the encapsulation efficiency (EE) of the PEG-PLGA / TMP drug-loaded nanoparticles did not change significantly in acidic medium ( Figure 3 D), which means that the drug-loaded nanoparticles can maintain good stability in the gastric fluid environment, thereby ensuring their structural integrity.
[0082] Experimental Example 4: In vitro release of drug-loaded nanoparticles
[0083] like Figure 4 As shown in Figure 2, the 48-hour release curves of PEG-PLGA / TMP nanoparticles and free TMP at 37°C were compared. In a pH 1.2 medium, free TMP rapidly dissolved 96.97% within 1 hour, while PEG-PLGA / TMP nanoparticles showed significant sustained release properties ( Figure 4 A). TMP release from the nanoparticles at pH 1.2 exhibited a biphasic pattern: approximately 70-75% of the total drug was rapidly released within the initial 10 hours, followed by a slow release phase. PEG-PLGA significantly delayed TMP degradation in acidic media, consistent with its stability under low pH conditions. In PBS at pH 6.8, the cumulative release rate of free TMP within 48 hours was only 58%, while that of PEG-PLGA / TMP nanoparticles reached 86%, indicating that PEG-PLGA promoted TMP release under this pH condition ( Figure 4 B) Under both pH conditions, the sustained-release performance of the PEG-PLGA / TMP nanoparticles was superior to that of free TMP, demonstrating that the nanoparticles of the present invention can be effectively delivered into the intestine in a substantially intact form. Therefore, it can be speculated that the PEG-PLGA / TMP nanoparticles can improve the oral bioavailability of TMP.
[0084] Experimental Example 5: Pharmacokinetic Test
[0085] The plasma concentration-time curve after administration of 20 mg / kg is as follows Figure 5 The pharmacokinetic parameters are summarized in Table 3.
[0086] Following oral administration of PEG-PLGA / TMP nanoparticles, plasma TMP concentrations rapidly reached a peak of 541.33±35.00 ng / mL at 0.5 hours, then gradually declined and remained above 30 ng / mL for 12 hours. In contrast, free TMP peaked much more rapidly at 417.51±23.34 ng / mL at 0.33±0.13 hours after oral administration and rapidly declined to below 30 ng / mL within 4 hours. Pharmacokinetic parameters further highlighted the advantages of the nanoparticles: the AUC0-∞, t1 / 2, and MRT of the nanoparticles were 2298±227 ng·h / mL, 2.47±0.19 hours, and 3.10±0.11 hours, respectively, compared to 814±99 ng·h / mL, 0.72±0.08 hours, and 1.27±0.11 hours for free TMP, respectively. Compared with free TMP, the bioavailability, t1 / 2 and MRT of the prepared PEG-PLGA / TMP nanoparticles increased by 2.82 times, 3.43 times and 2.44 times, respectively, indicating that the nanoparticles have a sustained-release effect and improve the oral bioavailability of TMP.
[0087] These results demonstrate that PEG-PLGA nanoparticles not only prolong systemic drug exposure through sustained release but also significantly enhance oral bioavailability. This improved performance is likely attributable to three synergistic mechanisms. First, TMP is dispersed in an amorphous form within the nanoparticles, avoiding the lattice energy required to dissolve crystalline drugs. This significantly increases their solubility and dissolution rate, leading to greater drug absorption into the bloodstream. Second, modification with the hydrophilic polymer PEG enhances the dispersibility and stability of the nanoparticles. Furthermore, PEG reduces the likelihood of nanoparticle recognition and phagocytosis by the reticuloendothelial system, thereby extending their circulation time in the body. Finally, based on previous stability testing, PEG-PLGA / TMP nanoparticles remain stable in acidic solutions, protecting TMP from degradation in the gastric acid environment and ensuring that the drug reaches the intestinal absorption site intact. Taken together, these properties facilitate the transport of nanoparticles across the epithelial barrier via transcellular, paracellular, and lymphatic pathways, effectively overcoming the absorption limitations of low-solubility TMP and ultimately improving oral bioavailability.
[0088] Table 3 In vivo pharmacokinetic parameters of TMP and PEG-PLGA / TMP nanoparticles after oral administration in rats (n=6)
[0089]
[0090]
[0091] Note: * Compared with TMP, the difference is statistically significant (P<0.01).
[0092] Abbreviation: AUC 0-t : Area under the curve from time 0 to time t; AUC 0- ∞: area under the curve from zero to infinity; C max : Peak plasma drug concentration, T max : time to peak; t1 / 2: elimination half-life; MRT: mean residence time; Vd: apparent volume of distribution; CL: clearance in vivo; F: relative bioavailability.
[0093] In vitro-in vivo correlation of PEG-PLGA / TMP drug-loaded nanoparticles Figure 6 As shown in Figure 2, there is a proportional relationship between the cumulative release of drugs in vitro and systemic absorption. As the former progresses, the latter increases synchronously. According to the literature, the coefficient of determination (R 2 ) between 0.49 and 0.80 indicates a strong correlation, while R 2 A value between 0.81 and 1 indicates a very strong correlation. Therefore, it can be concluded that there is a strong correlation between the in vivo absorption and in vitro release of PEG-PLGA / TMP drug-loaded nanoparticles. This strong correlation confirms that in vitro release profiles can reliably predict the in vivo absorption kinetics of TMP, providing guidance for the optimized design of TMP nanoformulations. Based on in vitro release data, excipient ratios and preparation parameters can be strategically adjusted to systematically improve bioavailability and achieve the desired therapeutic effect.
[0094] As can be seen from the above examples, the present invention provides a PEG-PLGA nanoparticle for enhancing the oral absorption of trimethoprim and a preparation method thereof. The present invention successfully prepared PEG-PLGA nanoparticles using an emulsion solvent evaporation method as an effective oral delivery system for TMP to improve its solubility and bioavailability. The nanoparticles obtained by the method of the present invention have a high drug loading (LC) of 34.0±1.6% and an encapsulation efficiency (EE) of 88.2±4.3%, a uniform particle size (245±40nm), and a PDI as low as 0.103±0.019. The nanoparticles of the present invention exhibit excellent stability: they maintain stable physical and chemical properties within 30 days of storage at 4°C, and there is no significant change in the encapsulation efficiency in an acidic medium, indicating that they can maintain structural integrity in a gastric fluid environment. In vitro release studies showed that PEG-PLGA / TMP nanoparticles exhibited sustained-release properties, exhibiting a biphasic release pattern in a pH 1.2 medium and accelerated release in a pH 6.8 medium. The release behavior conformed to the first-order kinetic model, dominated by Fickian diffusion. PXRD analysis confirmed that TMP existed in an amorphous state, resulting in a cumulative release rate of 86% over 48 hours at pH 6.8. In vivo pharmacokinetic studies showed that compared with free TMP, PEG-PLGA / TMP nanoparticles significantly prolonged the elimination half-life of TMP (t 1 / 2 ) to 2.47±0.19 hours (free TMP is 0.72±0.08 hours), and the oral bioavailability is increased by 2.82 times due to the prolonged circulation time in the body and the reduced degradation in the gastric environment. In vitro-in vivo correlation analysis showed that the determination coefficient (R 2 ) was 0.9623, further verifying the reliability of the design of PEG-PLGA / TMP nanoparticles, and its in vitro release curve can effectively predict the in vivo absorption kinetics. These results show that PEG-PLGA / TMP nanoparticles not only solve the inherent defects of TMP (such as low solubility and rapid clearance), but also significantly improve its oral bioavailability. The technical solution of the present invention highlights the potential of PEG-PLGA / TMP nanoparticles as an alternative to traditional formulations, which is expected to reduce the frequency of administration and improve the treatment effect of bacterial infections.
[0095] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.
Claims
1. A method for preparing PEG-PLGA nanoparticles for enhancing oral absorption of trimethoprim, characterized in that: The following steps are involved: 1) dissolving trimethoprim, polyethylene glycol, and poly(lactic acid-co-glycolic acid) in organic solvents to obtain a trimethoprim solution, a polyethylene glycol solution, and a poly(lactic acid-co-glycolic acid) solution, respectively; 2) adding the trimethoprim solution dropwise to the polyethylene glycol solution, and performing ultrasonic treatment to obtain a mixture solution; 3) adding the mixture solution to the poly(lactic acid-co-glycolic acid) solution to form an organic phase; 4) using polyvinyl alcohol solution as the aqueous phase, mixing the organic phase and the aqueous phase, and then performing ultrasonic treatment, evaporation, washing, and centrifugation in sequence to collect the precipitate; 5) Ultrasonic dispersion of the precipitate in water, followed by freeze-drying to obtain drug-loaded nanoparticles.
2. The preparation method according to claim 1, characterized in that In the step 1), the organic solvent comprises dichloromethane, and the mass ratio of the trimethoprim, polyethylene glycol and polylactic acid-glycolic acid copolymer is 30-45:80-110:350-450.
3. The preparation method according to claim 1 or 2, characterized in that The mass concentration of the trimethoprim solution is 1.5-4 mg / mL, the mass concentration of the polyethylene glycol solution is 6-7 mg / mL, and the mass concentration of the polylactic acid-glycolic acid copolymer solution is 22-30 mg / mL.
4. The preparation method according to claim 3, characterized in that The mass concentration of the polyvinyl alcohol solution is 0.5-2%, and the volume ratio of the water phase to the oil phase is 2-5:
1.
5. The preparation method according to claim 1, 2 or 4, characterized in that: In step 2) and step 4), the ultrasonic treatment is intermittent ultrasonic treatment, and the pulse cycle is: ultrasonic 4 seconds / pause 2 seconds; the ultrasonic treatment power is 200-300W, and the ultrasonic treatment time is independently 1-10 minutes.
6. The preparation method according to claim 5, characterized in that The evaporation temperature is 30-40° C., and the evaporation time is 5-20 minutes.
7. The preparation method according to claim 1 or 6, characterized in that The centrifugal speed is 14000-25000 rcf, the centrifugal time is 20-40 min, and the centrifugation is performed at 0-10°C.
8. The preparation method according to claim 7, characterized in that The freeze-drying treatment temperature is -90 to -70°C, and the freeze-drying treatment time is 20 to 30 hours.
9. PEG-PLGA nanoparticles for enhancing oral absorption of trimethoprim prepared by the preparation method according to any one of claims 1 to 8.